One-step lignocellulose depolymerization and saccharification to high sugar yield and less condensed isolated lignin. Issue 3 (6th January 2021) - Sadula, Sunitha; Rodriguez Quiroz, Natalia; Athaley, Abhay; Ebikade, Elvis Osamudiamhen; Ierapetritou, Marianthi; Vlachos, Dionisios G.; Saha, Basudeb
Abstract : The cost of sugar production remains a key challenge in future lignocellulosic biorefineries. Abstract : The cost of sugar production remains a key challenge in future lignocellulosic biorefineries. We demonstrate that ZnBr2, an inexpensive inorganic salt, provides nearly theoretical yields of glucose and xylose in one-step from poplar wood at 85 °C and short reaction times at molten salt hydrate (MSH) conditions without an acid. Catalytic depolymerization of the isolated MSH lignin, using a CoS2 catalyst, yields 17% phenol-like monomers compared to only 1% produced from the acidified MSH lignin. Reductive catalytic fractionation of MSH lignin over Ru/C resulted in two times higher total monomer yield compared to the AMSH lignin. Both the lignin samples were characterized using 2D HSQC NMR and the thioacidolysis method. Thioacidolysis studies reveal 8.4% and 1.8% of β-O-4 linkages in MSH and acidified MSH lignin, respectively. Thermodynamic modeling and 13 C NMR spectroscopy indicate that the effectiveness of this catalyst arises from the strong interaction of the Lewis acidic zinc cation (Zn 2+ ) with the coordinated water molecules resulting in hydrolysis of the metal aquo complex and to the salt-driven increase in the H + activity coefficient. Techno-economic analysis demonstrates that despite being slower, the ZnBr2 MSH media has cost advantages, compared to conventional hydrolysis and even to the LiBr and ZnBr2 AMSH, due to the higher quality of lignin.